2021
DOI: 10.3390/ijerph18094804
|View full text |Cite
|
Sign up to set email alerts
|

Preference towards HIV Self-Testing above Other Testing Options in a Sample of Men Who Have Sex with Men from Five European Countries

Abstract: We analyzed men who have sex with men (MSM) from Denmark, Germany, Greece, Portugal and Spain to identify who would choose HIV self-testing as their preferred testing method and assessed their preferred setting to acquire a self-testing kit and to confirm a reactive result. In 2016, we recruited an online sample of 3725 HIV-negative MSM. We used Poisson regression to identify factors associated with choosing self-testing as the preferred testing option. For those choosing it as their preferred option, we asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 32 publications
(39 reference statements)
0
6
0
Order By: Relevance
“…In a systematic review of HIVST among key populations, including MSM, eight out of 14 studies reporting on acceptability found high acceptability of HIVST (≥67%), five studies found moderate acceptability (66–34%), and one study found acceptability to be low [ 7 ]. Further, Hoyos et al found HIVST to be the preferred testing option for one-third of an online sample of MSM recruited in five European countries [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a systematic review of HIVST among key populations, including MSM, eight out of 14 studies reporting on acceptability found high acceptability of HIVST (≥67%), five studies found moderate acceptability (66–34%), and one study found acceptability to be low [ 7 ]. Further, Hoyos et al found HIVST to be the preferred testing option for one-third of an online sample of MSM recruited in five European countries [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Compared with traditional on-site testing, self-testing offers increased privacy and anonymity and is highly convenient since it does not require appointments or queuing [17]. According to the opinions of MSM recruited in online gay dating websites and apps in Spain, acceptability and potential use of HIV self-testing is high [18] and it is a highly valued option [19]. In fact, several clinical trials also support self-testing's capacity to increase testing frequency among MSM and other highly vulnerable populations [20,21] but there is little real-life data on its capacity to promote testing.…”
Section: Introductionmentioning
confidence: 99%
“…Thirty-three studies identified home-based self-testing or self-sampling as the preferred method of testing [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 22 , 23 , 24 , 26 , 29 , 31 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 ] ( Table 2 ). Three randomised controlled trials (RCT) found that HIVST increased testing frequency, and therefore was preferred by MSM compared to usual testing [ 17 , 21 , 54 ].…”
Section: Resultsmentioning
confidence: 99%
“…Eight studies identified that free/low-cost testing was an important consideration for MSM [ 17 , 18 , 26 , 42 , 50 , 55 , 56 , 71 ]. A mixed-method study exploring the acceptability of self-testing in the UK used data collected from self-completed questionnaires and oral fluid specimen collections of 999 MSM and conducted 12 expert focus groups with MSM, health professionals, community organisations, entrepreneurs and activists [ 49 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation